THE SPIRIT OF FEAR: ROME AND ABSOLUTISM (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
This article affirms that Enlightenment philosopher Montesquieu produced a historical and political theory based on the history of Rome. The main focus of this text is the association contained in the idea of a similarity between the Roman Empire and Oriental Despotism. For Montesquieu, corruption destroyed the spirit of freedom and virtue of the Roman Republic and founded an empire based on fear, which is the principle of despotism. The main source of analysis here is the book The spirit of the laws.